Analyzing the impact of entrepreneurial, market, and learning orientations on business performance in batik enterprises: a path analysis study in East Java, Indonesia - Djoko Poernomo; Hari Karyadi; Yuslinda Dwi Handini; Dwi Windradini; Khamdan Rifa’i; Nurul Widyawati Islami Rahayu; Mohammad Sawir (Cogent Business & Management)
This study examines the influence of entrepreneurial, market, and learning orientations on business performance in the batik industry, with competitive advantage as an intervening variable. Using Resource-Based View (RBV) theory, it highlights how these orientations shape competitive advantage, which mediates their impact on performance. Data were collected from 80 batik business owners in East Java, Indonesia, using a quantitative approach and path analysis to identify direct and indirect relationships. Findings reveal that entrepreneurial and learning orientations significantly enhance competitive advantage, while market orientation boosts performance without directly influencing competitive advantage. The mediated effect of competitive advantage is evident only for entrepreneurial orientation, as learning orientation’s influence does not fully translate into performance. The study underscores the need to foster entrepreneurial orientation and competitive advantage for business success. However, the omission of factors like innovation capability and sector-specific challenges limits its scope, pointing to future research opportunities. Practical implications suggest policymakers and business owners should combine market orientation with long-term learning strategies to sustain competitive advantage. While focused on batik enterprises, the insights are applicable to other industries facing similar challenges.